(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Haryana State came into existence on 1st November, 1966 and the Punjab Gram Panchayat Act, 1952 was made applicable to the PRIs in Haryana followed by the 73rd Constitutional amendment in 1992, the Haryana Panchayati Raj Act, 1994 was framed which came into force w.e.f. April 22, 1994. Thereafter Haryana Panchayati Raj Election Rules, 1994 were formulated on 24th August, 1994 followed by Haryana Panchayati Rules, 1995, notified on 16th February1995. Subsequently the Haryana Panchayati Raj Finance Budget Accounts Audit Taxation and works rules 1996 were also notified on 14th August, 1996. Under the Haryana Panchayati Raj Act 1994, the Panchayati Raj Institutions have been entrusted with duties functions related to all the 29 subjects listed in Eleventh Schedule of the Constitution[1]Three-tier structure of Panchayati Raj institutions in Haryana was introduced at its inception. Haryana as a state was carved out of erstwhile Punjab state. Therefore, it has adopted The Punjab Gram Panchayat Act, 1952, and The Punjab Block Samiti and Zila Parishad Act, 1961. The three- tier system of Panchayati Raj as introduced earlier in the state, included Gram Panchayat, Block Samiti and Zila Parishad. There is a statutory body called Gram Sabha comprising all the adult residents of a village besides the above stated three-tiers. Zila Parishads, the apex body of PR, were abolished in 1973 in the state following the recommendations of Maru Singh Malik Committee.[2] Since then, Haryana was having the two-tier structure of Panchayati Raj, i.e., Gram Panchayat and Block Samiti. However, it could not fulfill the goal of democratic decentralization in the state[3]After the creation of Haryana as separate state in 1966, the elections of Panchayati Raj institutions were not conducted at regular intervals and thus, the powers of these bodies were concentrated in the hands of bureaucracy. It indicates the lack of political will of the state government towards the efficient functioning of PR in the state. In compliance with the 73rd Constitutional Amendment, an Act called The Haryana Panchayati Raj Act was enforced on April 22, 1994, replacing the earlier Acts enacted and adopted in the state. The present Act provides for the three-tier system of PR, viz., Gram Panchayat at village level, Block Samiti at block level and Zila Parishad at district level.[4]